ANALISIS KEPUASAN PELANGGAN BUS DAMRI CABANGLAMPUNG - Cornelius Ary Kristiyanto; Yunada Arpan (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2020)
Perum DAMRI is a company which running in services area. In applying the objectives of the company that want to get high profits, company must provide quality services that can be accepted by customers, especially in Lampung. The formulation of problem inthis research